Application of EMBM to Structure‐Based Design of Warheads for Protease Inhibitors. Issue 1 (24th October 2013) - Traube, Tamar; Shokhen, Michael; Albeck, Amnon
Abstract Most CADD tools handle non‐covalent enzyme inhibitors, despite the growing interest of the pharma industry in covalent inhibitors. We have recently introduced an enzyme mechanism‐based method, EMBM, as a computational tool for binding trend analysis and prediction of chemical sites (CS) of reversible covalent enzyme inhibitors. In the current study we demonstrate the utility of EMBM to structure‐based applications. In this mode, the energy of the enzyme‐inhibitor covalent bond is accounted for by the W1 and W2 covalent descriptors we have developed, whereas the non‐covalent interactions between the inhibitor CS and the enzyme active site can be estimated directly on the 3D structure of the enzyme‐inhibitor complex.